2021
DOI: 10.1002/ep.13646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slope tower angle and thermal storage media on flexibility solar chimney power plant performance

Abstract: Floating tower projects in solar chimney power plant are emerging with considerable interest. However, high chimney tower might be under great pressure from wind blow. Use of flexible fabric material for the tower might reduce the constraint on the chimney and reduce the cost. The present work is devoted to the study of the solar tower inclination impact on the efficiency of the solar chimney power plant (SCPP).The considered inclination angles of the tower are 15 , 22 , and 30 . In addition, waterbed is laid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They emphasized that when gravel is used on the ground, a higher surface temperature could be achieved than when soil is used. Based on the Manzanares pilot plant, Semai and Bouhdjar [121] estimated the performance of a possible SCPP plant in Adrar, in the southwestern region of Algeria. In addition to the pilot plant, evaluated the effect of a floating chimney and an additional energy storage unit on the system, and analyzed the optimum power output.…”
Section: Properties Soil Gravel Sandmentioning
confidence: 99%
“…They emphasized that when gravel is used on the ground, a higher surface temperature could be achieved than when soil is used. Based on the Manzanares pilot plant, Semai and Bouhdjar [121] estimated the performance of a possible SCPP plant in Adrar, in the southwestern region of Algeria. In addition to the pilot plant, evaluated the effect of a floating chimney and an additional energy storage unit on the system, and analyzed the optimum power output.…”
Section: Properties Soil Gravel Sandmentioning
confidence: 99%
“…Golzardi et al 3 evaluated the influence of thermal energy storage systems on the operation and performance of solar updraft tower PPs. Semai et al 4 examined the influence of inclination angle of slope tower and thermal storage media on the adaptability of solar chimney power plant (SCPP) operation. Abdelsalam et al 5 conducted a study to investigate the feasibility of integrating a cooling tower (CT) and a conventional solar power plant (SPP) to generate electricity and desalinate seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies have shown that divergent chimneys outperform cylindrical chimneys, with a 54% improvement in performance (9) . A study (10) examines the impact of chimney inclination (15 , and 30 • ) on the performance of freestanding updraft chimney solar power plants. It considers a straight rigid tower and a tilting tower under wind forces.…”
Section: Introductionmentioning
confidence: 99%